Determination of the Levels of Heavy Metals and Formaldehyde in Baby Clothes in South Africa: A Case Study of Stores in the Greater Cape Town Region - P. Nyamukamba; C. Bantom; Z. Mququ; T. Ngcobo; S. Isaacs (Journal of Spectroscopy)
Herein, we report on the determination of formaldehyde, pH, and heavy metals (Pb, As, Co, Cr, Ni, and Cd) in various baby apparel (cotton, polyester, nylon, elastane, and polyethylene) of different colours (light, medium, and dark) purchased from both high-end and low-end market stores. The concentrations of the heavy metals were determined by inductively coupled plasma (ICP) after wet digestion and also after extraction using artificial sweat for a selected range of skin-contact baby apparel. The relative standard deviation for the determination of all heavy metals was less than 5% except for nickel which was 10.49%. The concentrations of the heavy metals in wet digested samples were found to be in the following range: Pb (0.02–23.662 mg/kg), As (0.009–0.033 mg/kg), Co (0.001–1.053 mg/kg), Cr (0.053–6.373 mg/kg), Ni (0.039–36.715 mg/kg), and Cd (0.001–0.914 mg/kg), whereas the concentrations in artificial sweat extracted samples were in the following range: Pb (0.006–1.658 mg/kg), As (not detected), Co (0.001–1.05 mg/kg), Cr (0.112–0.371 mg/kg), Ni (0.062–0.121 mg/kg), and Cd (0.001–0.018 mg/kg). The highest concentrations of Pb, Cr, and Co after wet digestion were found in baby apparel purchased from low-end market stores, whereas for As, Ni, and Cd were from high-end market stores. All the samples had a formaldehyde concentration within the acceptable limits recommended by Oeko-Tex. Out of the thirty-four samples analysed, fifteen samples were found to have a pH higher than Oeko-Tex limits. The pH values for the samples that exceeded the Oeko-Tex limits were in the alkali region, and the highest was 11.31 which exceeded by 3.81.